10 anos de MINUSTAH: uma avaliação de suas consequências políticas para o Brasil - Anselmo, André Luiz Ramos Pereira (2014)
The peacekeeping literature is plentiful with examples of analysis of the operations’ performance. These analyzes study the fulfillment of the mandate, or the effects on the host state. But few studies address the consequences of participation for the States that send troops. Trying to help fill this gap, this work aims to understand the participation and the Brazilian role in the United Nations Mission for the Stabilization of Haiti - MINUSTAH helped Brazil reach their goals. Using a mixed approach, troop contribution and budgetary data were analyzed, as well as official documents and, finally, 08 interviews with military and civilian experts were conducted. Based on the applied state goals model, I have studied if the presence in Haiti allowed Brazil to signal their goals for the international community, reform its institutions, the military among them, and if there were any budgetary needs to contribute to the mission. The evidence analyzed suggest that the balance of the mission is mixed. Although some aspects show definite improvements, others are irrelevant or suffer from the maintenance of antiquated military culture.